Proteomic Identification and Functional Analysis of Babesia microti Reveals Heparin-Binding Proteins - Yu Chun Cai; Bin Xu; Yan Hong Chu; Ying Fang Yu; Jia Hui Sun; Zi Ran Mo; Han Yin Yang; Shu Ning Yan; Mu Xin Chen; Jia Xu Chen (Journal of Tropical Medicine)
Glycosaminoglycan (GAG) molecules on the surface of red blood cells play an important regulatory role in the invasion of merozoites of apicomplexan protozoa. Heparan sulfate, a type of GAG molecule, has been identified as an important receptor facilitating the invasion of red blood cells by these parasites. Proteins in the parasite that exhibit strong affinity for heparin may play a pivotal role in this invasion process. This study aims to use proteomics to identify Babesia microti proteins with high binding affinity to heparin. Bioinformatics was utilized to analyze the subcellular localization and biological functions of these proteins. Candidate genes encoding proteins with strong heparin affinity will be expressed in a prokaryotic system to produce recombinant proteins. The interaction between these recombinant proteins and heparin will be characterized through heparin-binding experiments and other methods. Initially, a mouse model of B. microti was established and high-density B. microti were obtained. Heparin affinity chromatography was then used to purify natural B. microti proteins that can bind to heparin, identifying 186 B. microti proteins via ESI-MS that specifically interact with heparin. Further studies were carried out to analyze those specific proteins with unique peptide segments of two or more, yielding 15 B. microti proteins, most of which are cell surface proteins and secretory proteins. Based on mass spectrometry identification and subsequent analyses, BMSA5-1-1, B. microti peptidyl-prolyl cis-trans isomerase (BmPPIase), and chaperonin were selected for further study due to their potential impact on the invasion of red blood cells by B. microti. These candidate proteins were expressed as recombinant proteins using a prokaryotic expression system. In vitro heparin-binding assays demonstrated that these recombinant proteins specifically bind to heparin. Notably, BmPPIase and chaperonin recombinant proteins exhibited activity in specific heparin binding. Molecular interaction studies further confirmed the strong interaction between BmPPIase and heparin. In conclusion, this study used proteomic methods to identify 186 specific B. microti proteins with specific binding affinity to heparin, providing in-depth analysis of 15 key proteins. The findings confirmed that BmPPIase and chaperonin specifically bind to heparin, with molecular interaction experiments substantiating the strong interaction between BmPPIase and heparin.